Reply to “Correspondence: Androgen receptor mRNA in glioblastoma: a reliable marker of tumor burden or a statistical artefact?” - Larysa Liubych; Lorenz Hahn; Raja Hollnagel; Maria Karolin Streubel; Deepak Ailani; Jan Leppert; Harald Krenzlin; Jakob Matschke; Celina Soltwedel; Nicole Borgardt; Susanne Behling; Oksana Zemskova; et al. (Molecular Biology Reports, 2026)

Androgen receptor expression in glioblastoma: molecular profiling and association with tumor burden - Larysa Liubych; Lorenz Hahn; Raja Hollnagel; Maria Karolin Streubel; Deepak Ailani; Jan Leppert; Harald Krenzlin; Jakob Matschke; Celina Soltwedel; Nicole Borgardt; Susanne Behling; Oksana Zemskova; et al. (Molecular Biology Reports, 2026)

Estimating electrical distribution network length and capital investment needs from real-world topologies and land cover data - Lenard Rüde; Moritz Wussow; Miguel Heleno; Gunther Gust; Dirk Neumann (Energy Policy, 2024)

Climate variability in a 3.8 Ma old sedimentary record from the hyperarid Atacama Desert - Felix L. Arens; Jenny Feige; Alessandro Airo; Christof Sager; Lutz Hecht; Lucas Horstmann; Felix E.D. Kaufmann; Johannes Lachner; Thomas Neumann; Norbert Nowaczyk; Ferry Schiperski; Peter Steier; et al. (Global and Planetary Change, 2024)

Club cell protein (CC16) in serum as an effect marker for small airway epithelial damage caused by diesel exhaust and blasting fumes in potash mining - Savo Neumann; Swaantje Casjens; Frank Hoffmeyer; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Jörg Giesen; Volker Neumann; Dirk Taeger; Dirk Pallapies; Thomas Birk; et al. (International Archives of Occupational and Environmental Health, 2024)
Objective The effect marker club cell protein (CC16) is secreted by the epithelium of the small respiratory tract into its lumen and passes into the blood. Increased amounts of CC16 in serum are observed during acute epithelial lung injury due to air pollutants. CC16 in serum was determined as part of this cross-sectional study in underground potash miners on acute and chronic health effects from exposures to diesel exhaust and blasting fumes. Methods Nitrogen oxides, carbon monoxide, and diesel particulate matter were measured in 672 workers at a German potash mining site on a person-by-person basis over an early shift or midday shift, together with CC16 serum concentrations before and after the respective shift. CC16 concentrations and CC16 shift-differences were evaluated with respect to personal exposure measurements and other quantitative variables by Spearman rank correlation coefficients. CC16 shift-differences were modeled using multiple linear regression. Above-ground workers as reference group were compared to the exposed underground workers. Results Serum concentrations of CC16 were influenced by personal characteristics such as age, smoking status, and renal function. Moreover, they showed a circadian rhythm. While no statistically significant effects of work-related exposure on CC16 concentrations were seen in never smokers, such effects were evident in current smokers. Conclusion The small airways of current smokers appeared to be vulnerable to the combination of measured work-related exposures and individual exposure to smoking. Therefore, as health protection of smokers exposed to diesel exhaust and blasting fumes, smoking cessation is strongly recommended.

Impact of diesel exhaust exposure on urinary 1-hydroxypyrene in underground salt and potash workers - Swaantje Casjens; Savo Neumann; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Thomas Birk; Jörg Giesen; Volker Neumann; Dirk Pallapies; Jürgen Bünger; Heiko U. Käfferlein; et al. (International Journal of Hygiene and Environmental Health, 2023)

Underground salt and potash workers exposed to nitrogen oxides and diesel exhaust: assessment of specific effect biomarkers - Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Katrin Rühle; Annette M. Bachand; Lori Crawford; Kenneth A. Mundt; Jürgen Bünger; Dirk Pallapies; Dirk Taeger; Swaantje Casjens; Anja Molkenthin; et al. (International Archives of Occupational and Environmental Health, 2022)
Purpose Occupational exposure limits (OEL) for nitrogen oxides (NO, NO 2 ) and diesel exhaust (EC-DPM) were reassessed by the German authorities in 2016/2017. We performed a clinical cross-sectional study among salt and potash underground workers exposed to these substances at relatively high levels to examine possible indicators of acute effects on workers’ health. Methods We measured post- versus pre-shift differences in cardiovascular, inflammatory, immune, and respiratory effect biomarkers and assessed their associations with personal exposures measured during the same shift. We also compared post- versus pre-shift differences in biomarker levels between exposure groups defined based on work site and job type. Results None of the above-ground workers exceeded the OEL for NO 2 and only 5% exceeded the OEL for EC-DPM exposure. Among underground workers, 33% of miners and 7% underground maintenance workers exceeded the OEL for NO 2 ; the OEL for EC-DPM was exceeded by 56% of miners and 17% of maintenance workers. Some effect biomarkers (thrombocytes, neutrophils, MPO, TNF-α, IgE, FeNO) showed statistically significant differences between pre- versus post-shift measurements; however, there were no consistent associations between pre- and post-shift differences and exposure group or personal exposure measurements during the shift. Conclusions We did not find evidence of associations between workplace exposure to NO, NO 2 or EC-DPM and clinically relevant indicators of acute cardiovascular, inflammatory and immune, or respiratory effects among salt and potash underground workers in Germany.

New phylogenetic insights into the African catfish families Mochokidae and Austroglanididae - Frederic D. B. Schedel; Albert Chakona; Brian L. Sidlauskas; Michael O. Popoola; Nadine Usimesa Wingi; Dirk Neumann; Emmanuel J. W. M. N. Vreven; Ulrich K. Schliewen (Journal of Fish Biology, 2022)
Several hundred catfish species (order: Siluriformes) belonging to 11 families inhabit Africa, of which at least six families are endemic to the continent. Although four of those families are well‐known to belong to the ‘Big‐Africa clade’, no previous study has addressed the phylogenetic placement of the endemic African catfish family Austroglanididae in a comprehensive framework with molecular data. Furthermore, interrelationships within the ‘Big‐Africa clade’, including the most diverse family Mochokidae, remain unclear. This study was therefore designed to help reconstruct inter‐ and intrarelationships of all currently valid mochokid genera, to infer their position within the ‘Big Africa clade’ and to establish a first molecular phylogenetic hypothesis of the relationships of the enigmatic Austroglanididae within the Siluriformes. We assembled a comprehensive mitogenomic dataset comprising all protein coding genes and representing almost all recognized catfish families ( N = 33 of 39) with carefully selected species ( N = 239). We recovered the monophyly of the previously identified multifamily clades ‘Big Asia’ and ‘Big Africa’ and determined Austroglanididae to be closely related to Pangasiidae, Ictaluroidea and Ariidae. Mochokidae was recovered as the sister group to a clade encompassing Auchenoglanididae, Claroteidae, Malapteruridae and the African Schilbeidae, albeit with low statistical support. The two mochokid subfamilies Mochokinae and Chiloglanidinae as well as the chiloglanid tribe Atopochilini were recovered as reciprocally monophyletic. The genus Acanthocleithron forms the sister group of all remaining Mochokinae, although with low support. The genus Atopodontus is the sister group of all remaining Atopochilini. In contrast to morphological reconstructions, the monophyly of the genus Chiloglanis was strongly supported in our analysis, with Chiloglanis macropterus nested within a Chiloglanis sublineage encompassing only other taxa from the Congo drainage. This is an important result because the phylogenetic relationships of C. macropterus have been controversial in the past, and because we and other researchers assumed that this species would be resolved as sister to most or all other members of Chiloglanis . The apparent paraphyly of Synodontis with respect to Microsynodontis provided an additional surprise, with Synodontis punu turning out to be the sister group of the latter genus.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Anaerobic treatment of residuals from tanks transporting food and fodder - Van Than Nguyen; Erik Beyer; Jan Neumann; Dirk Awe; Wolfgang Pfeiffer; Jens Tränckner (Environmental Science and Pollution Research, 2019)

Rediscovery of type material of the bioerosional trace fossil Talpina von Hagenow, 1840 and its ichnotaxonomic implications - Max Wisshak; Christian Neumann; Dirk Knaust; Mike Reich (PalZ, 2017)

Aquifer community structure in dependence of lithostratigraphy in groundwater reservoirs - Andrea Beyer; Michael Rzanny; Aileen Weist; Silke Möller; Katja Burow; Falko Gutmann; Stefan Neumann; Julia Lindner; Steffen Müsse; Hanka Brangsch; Jennifer Stoiber-Lipp; Martin Lonschinski; et al. (Environmental Science and Pollution Research, 2015)

The effect of skin fatty acids on Staphylococcus aureus - Yvonne Neumann; Knut Ohlsen; Stefanie Donat; Susanne Engelmann; Harald Kusch; Dirk Albrecht; Michael Cartron; Alexander Hurd; Simon J. Foster (Archives of Microbiology, 2015)

Import and export of biological samples from tropical countries–considerations and guidelines for research teams - Swen C. Renner; Dirk Neumann; Michael Burkart; Ute Feit; Peter Giere; Andreas Gröger; Axel Paulsch; Cornelia Paulsch; Mario Sterz; Katrin Vohland (Organisms Diversity & Evolution, 2012)

Wie falten Membranproteine? — Schritt für Schritt!? - Jennifer Neumann; Noreen Klein; Dirk Schneider (BIOspektrum, 2012)

On the Photophysical Properties of New Luminol Derivatives and their Synthetic Phthalimide Precursors - Raúl Pérez-Ruiz; Robert Fichtler; Yrene Diaz Miara; Matthieu Nicoul; Dominik Schaniel; Helfried Neumann; Matthias Beller; Dirk Blunk; Axel G. Griesbeck; Axel Jacobi von Wangelin (Journal of Fluorescence, 2010)

The Role of Corneocytes in Skin Transport Revised—A Combined Computational and Experimental Approach - Steffi Hansen; Arne Naegel; Michael Heisig; Gabriel Wittum; Dirk Neumann; Karl-Heinz Kostka; Peter Meiers; Claus-Michael Lehr; Ulrich F. Schaefer (Pharmaceutical Research, 2009)

Photo‐identification of short‐beaked common dolphins (Delphinus delphis) in north‐east New Zealand: A photo‐catalogue of recognisable individuals - Dirk R. Neumann; Alexandra Leitenberger; Mark B. Orams (New Zealand Journal of Marine and Freshwater Research, 2002)
Photo‐identification has been established as a helpful tool in cetacean research. However, no study to date has attempted to apply this method to short‐beaked common dolphins (Delphinus delphis L.). We present here the results of two studies that were conducted concurrently in Mercury Bay and the Hauraki Gulf on the north‐east coast of New Zealand's North Island. Methods for distinguishing between individual dolphins are discussed. Sighting records of recognisable individuals indicate that some common dolphins move between Mercury Bay and the Hauraki Gulf (100 km distance), as well as between Mercury Bay and Whakatane (200 km distance). Common dolphin abundance and site fidelity appeared to be greater in the Hauraki Gulf than in Mercury Bay. A selection of photographs of distinct individuals is presented to allow future studies to compare their sighting records to ours, which may help establish the extent of home ranges, site fidelity, and possibly even longevity for common dolphins.

Seasonal movements of short‐beaked common dolphins (Delphinus delphis) in the north‐western Bay of Plenty, New Zealand: Influence of sea surface temperature and El Niño/La Niña - Dirk R. Neumann (New Zealand Journal of Marine and Freshwater Research, 2001)
Movement patterns of small cetaceans are influenced by a great number of variables including prey availability, sea floor profile, thermocline, oxygen minimum layer, and sea surface temperature (SST). Presented here are data on short‐beaked common dolphins (Delphinus delphis L.) in New Zealand, showing a seasonal offshore‐shift in their distribution, which appears to be correlated with SST. D. delphis moved from a mean distance of 9.2 km (SD = 4.42) from shore in spring and summer to a mean distance of 20.2 km (SD = 3.86) from shore in autumn. During warmer La Nina conditions their mean distance from shore was further reduced to only 6.2 km (SD = 2.56), and offshore movement was delayed by a month. Worldwide, D. delphis can be found throughout a wide range of sea temperatures, and it is therefore unlikely that SST is the primary factor influencing their distribution. It is hypothesised, that SST influences the distribution of D. delphis prey, which in turn affects their seasonal movements.

AGONISTIC BEHAVIOR IN HARBOR SEALS ( PHOCA VITULINA ) IN RELATION TO THE AVAILABILITY OF HAUL‐OUT SPACE - Dirk R. Neumann (Marine Mammal Science, 1999)
A bstract The hypothesis that haul‐out space is a contested resource among harbor seals ( Phoca vitulina ) was tested by comparing the number of agonistic interactions and the time devoted to them, at a haul‐out with unlimited space and a haul‐out with limited space, in Humboldt County, California. 798 agonistic interactions were recorded in 160 h of observation. The average number of agonistic interactions per seal per hour and the time spent on these interactions were significantly higher at the site with limited haul‐our space ( P n = 20). At this restricted site, the frequency of agonistic interactions was positively correlated with seal density ( r = 0.61, P n = 20), as was time spent on agonistic interactions ( r = 0.84, P n = 20). Size, sex, and age‐class of individuals all influenced agonistic interactions. In 72.5% of displacements, smaller seals were displaced by larger ones. This may support claims that some harbor seal populations maintain a size‐based dominance hierarchy. The results of this study support the hypothesis that there is competition among harbor seals for suitable haul‐out space where this resource is limited. The outcome of these interactions may be predicted, at least in part, by theoretical models on pay‐off asymmetries, resource holding power, and the prior residency effect.

Remains of woody plants from Saouga, a medieval west African village - Katharina Neumann; Stefanie Kahlheber; Dirk Uebel (Vegetation History and Archaeobotany, 1998)